Language attitudes of BIPA students (Indonesian for foreign speakers) towards Indonesian - Hidayatullah, Asep; Mulyati, Yeti; Saputra, Dedi; Lixian, Xiao; Waeno, Mahamadaree (BAHASTRA, 2023)
Having a positive attitude towards Indonesian is a necessity. To have good Indonesian language skills, BIPA students must have a positive attitude towards Indonesian. This study aims to describe the language attitudes of BIPA students towards Indonesian. The method used in this research is descriptive method. The data used in this study were collected through a questionnaire technique. The statements given consist of three aspects, namely language loyalty, language pride, and awareness of language rules. Data obtained through a questionnaire, processed quantitatively. As a result, most BIPA students (71.81%) have a positive attitude towards Indonesian.